Workshop Strategi Revolusioner Pembelajaran Modern Melalui Integrasi Teknologi Cerdas dan Platform Media Sosial bagi Pendidikan Generasi Digital - Hamu, Fransiskus Janu (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
Education in the current digital era demands the use of smart technology and social media platforms in the learning process to suit the character of the digital generation. However, the competence of lecturers in Indonesia in this regard is still limited. Therefore, the workshop